Facile synthesis of schwertmannite@akaganeite core/shell nanostructure from pickling waste liquor: Formation mechanism and potential application. (1st July 2020) - Kang, Feifei; Wu, Meng; Xiao, Bing; Chen, Rufen; Wei, Yu; Liu, Hui; Wu, Na
Abstract: An environmentally friendly and low-cost synthesis of schwertmannite@akaganeite (Sch@Aka) core/shell nanostructure was achieved from hydrochloric pickling waste liquor (HPWL). The Sch@Aka nanostructure had a pincushion-like shape composed of radially well-aligned nanorods with an average length of about 250 nm and a mean diameter of about 60 nm. Trace SO4 2− ions played a key role in the formation of the Sch@Aka nanostructure. In the presence of Fe 3+, Cl − and trace SO4 2− ions, schwertmannite was preferentially nucleated and then served as a core for akaganeite growth. The novel Sch@Aka nanostructure not only exhibited a higher adsorption capacity (43.0 mg g −1 ) for heavy metal Cr(VI) ions, but also delivered a larger reversible storage capacity of 1245 mA h·g −1 with Coulombic efficiency of close to 82% as the anode material in Li-ion batteries, indicating its potential application value. Graphical abstract: A novel pincushion-like Sch@Aka core/shell nanostructure was prepared through a low-cost and green procedure using steel pickling waste liquor as raw material. Image 102046 Highlights: A novel Sch@Aka core/shell structure was prepared from steel pickling waste liquor. Sch-phase is preferentially nucleated and serves as a template for β-FeOOH growth. Sch@Aka exhibits a high adsorption performance for the removal of Cr(VI). Sch@Aka can be used as a low-cost anode material in Li-ion batteries.